Harnessing Artificial Intelligence in Higher Education: Balancing Innovation and Ethical Challenges - Aprianto, Ronal; Lestari, Etty Puji; Sadan; Fletcher, Eamon (International Transactions on Education Technology (ITEE), 2024)
The development of Artificial Intelligence (AI) in higher education has created new opportunities while presenting major challenges. This research aims to explore the impact of AI on higher education, both in terms of benefits and risks that may arise in the future. AI has opened up opportunities to personalize learning experiences, automate administrative processes, and support innovation in curriculum development, potentially improving educational effectiveness. However, there are also concerns regarding the digital divide, data privacy, ethical considerations, and the readiness of educators and institutions to deal with these technological changes. This research uses a literature review approach by analyzing current research on AI implementation in higher education institutions. It also compares case studies from several developed and developing countries to gain a broader picture of the global influence of AI in the education sector. The results show that while AI can have a positive impact in terms of more efficient learning and more effective operations, challenges in terms of equitable access and transparency must be addressed. The novelty of this research lies in the comprehensive analysis of the long-term implications of AI on higher education, as well as the strategies that institutions need to implement to maximize the benefits of AI and minimize the risks. This research makes an important contribution to education stakeholders in understanding the importance of responsible AI adoption to create an inclusive and sustainable educational environment.